Análise da distribuição espacial da perda de solo na bacia hidrográfica do Ribeirão Vermelho-MS - EDWINA SANTOS DA COSTA (2024)
Soil preservation is as crucial to sustaining life as water, making it an essential task in environmental conservation. Watersheds have emerged as ideal units for environmental planning, allowing for various studies, including the analysis of soil erosion. Although erosion is a natural phenomenon, accelerated soil erosion has become a widely studied environmental challenge, with emphasis on effective methods. In this context, the Universal Equation of Soil Losses Revised (EUPSR), a model designed to estimate average soil losses, stands out as a widely used tool. The aim of this research was to analyze the spatial distribution of soil loss in the Ribeirão Vermelho watershed (BHRV), located in the municipalities of Aquidauana (63.65%) and Dois Irmãos do Buriti (36.35%) in the state of Mato Grosso do Sul. To this end, data was collected on rainfall (and subsequent correction), soils, topography and the use and management of the study area, using QGIS 3.28 software as geoprocessing support. The results obtained revealed a variability in water erosivity, ranging from 8,413.65 to 8,773.07 MJ mm/ha h year, with an average of 8,628.75 MJ mm/ha h year. Soil erodibility was most pronounced in the Litholic Neosols, covering around 26.60% of the area, with a value of 0.1129. The topographical variables highlighted the direct influence of the relief components on the erosion process, while the use factors and conservation practices highlighted the existing activities. In 2000, 38.34% of the area was covered by native vegetation, and 60.41% was occupied by pasture. In 2020, the vegetation class saw a slight reduction of 1.13%, totaling 37.21%, while pasture decreased by 19.44%, representing approximately 40.96% of the area. Forestry, present since 2003, occupied around 18.19% of the area in 2020. Soil loss reached a maximum value of 220.01 t/ha/year. Currently, in the field, there was a significant presence of forestry, sugar cane cultivation occupying a small part of the area, as well as the presence of livestock, characterizing the main activities in the region. Given the complexity and urgency of mitigating soil erosion, the analysis of the spatial distribution of soil loss carried out in the Ribeirão Vermelho watershed highlights the importance of integrated approaches, emphasizing the ongoing need for monitoring and implementing sustainable practices to preserve this vital resource for future generations.